P70-T Results of neurophysiological tests in a child with pandysautonomia. Issue 7 (July 2019) - Gergont, Aleksandra; Kroczka, Sławomir; Kaciński, Marek
Abstract : Background: Pandysautonomia can be associated not only with acute loss of autonomic functions leading to syncopes, blood pressure and heart rate changes but also can affect afferent functions of peripheral nerves, resulting in loss of motor functions. Aim: The aim of this study was to present tests to the evaluate autonomic function that are available to the clinician and significance of neurophysiological methods in the differential diagnosis of dysautonomia. Methods: We present a case report of a 16-year-old girl, admitted to the hospital after syncope. Two months earlier she suffered from upper respiratory tract infection, followed by severe gastroparesis, urine retention, sweating and pupillary disturbances. On the first day of hospitalization the child refused to walk. Several tests including electromyography, electroneurography, miastenic test, videoelectroencephalography and head-up tilt test with electrocardiography were performed. Biofeedback as one of therapeutic methods was introduced. Results: Autoimmune autonomic ganglionopathy was diagnosed with the postural orthostatic tachycardia syndrome. A significant clinical improvement was achieved after plasma exchange. Conclusion: Generalized autonomic failure can occur as a result of many diseases that affect autonomic pathways. The role of electrophysiological methods and autonomic testing is to increase sensitivity and specificity in the detection and differentiation of dysautonomia.